Nutritional Preconditioning of Apigenin Alleviates Myocardial Ischemia/Reperfusion Injury via the Mitochondrial Pathway Mediated by Notch1/Hes1. (20th March 2019) - Huang, Huang; Lai, Songqing; Luo, Yong; Wan, Qing; Wu, Qicai; Wan, Li; Qi, Wanghong; Liu, Jichun
Abstract : Apigenin (Api), a natural flavone found in high amounts in several herbs, has shown potent cardioprotective effects in clinical studies, although the underlying mechanisms are not clear. We hypothesized that Api protects the myocardium from simulated ischemia/reperfusion (SI/R) injury via nutritional preconditioning (NPC). Rats fed with Api-containing food showed improvement in cardiac functions; lactate dehydrogenase (LDH) and creatine phosphokinase (CPK) activities; infarct size; apoptosis rates; malondialdehyde (MDA) levels; caspase-3, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) activities; and ferric reducing antioxidant power (FRAP) compared to those fed standard chow following SI/R injury. In addition, Api pretreatment significantly improved the viability, decreased the LDH activity and intracellular reactive oxygen species (ROS) generation, alleviated the loss of mitochondrial membrane potential (MMP), prevented the opening of the mitochondrial permeability transition pore (mPTP), and decreased the caspase-3 activity, cytochrome c (Cyt C) release, and apoptosis induced by SI/R in primary cardiomyocytes. Mechanistically, Api upregulated Hes1 expression and was functionally neutralized by the Notch1 γ -secretase inhibitor GSI, as well as the mPTP opener atractyloside (Atr). Taken together, Api protected the myocardium against SI/R injury via the mitochondrial pathway mediated by the Notch1/Hes1 signaling pathway.